2021
DOI: 10.1111/joop.12337
|View full text |Cite
|
Sign up to set email alerts
|

Manager narcissism and employee silence: A socio‐analytic theory perspective

Abstract: Employee silence is detrimental to organizations, and managers high in narcissism may create conditions that indirectly promote employee silence. Drawing on socio‐analytic theory, in three samples (Ns = 79, 125, and 119), we investigated whether employees’ perceptions of manager trustworthiness mediated the relation between manager trait narcissism and employee silence, and whether this mediation was moderated by a social skill, apparent sincerity. We found that the three samples largely supported our research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…Since affective trust is a reliable indicator of a sense of safety to take risks in close relationships, such as leader-subordinate relationships (Mayer et al, 1995;Ng & Feldman, 2013b), we expect that subordinates who affectively trust their leader will feel safe to take risks at the workplace (Schaubroeck et al, 2011). Specifically, trusting subordinates are less likely to withhold their ideas from leaders (Hamstra et al, 2021) and more likely to communicate them via voice behaviour (Gao et al, 2011;Ng & Feldman, 2013b, 2015.…”
Section: Predicting Voice Behaviour: the Mediating Role Of Affective Trust In The Leadermentioning
confidence: 99%
“…Since affective trust is a reliable indicator of a sense of safety to take risks in close relationships, such as leader-subordinate relationships (Mayer et al, 1995;Ng & Feldman, 2013b), we expect that subordinates who affectively trust their leader will feel safe to take risks at the workplace (Schaubroeck et al, 2011). Specifically, trusting subordinates are less likely to withhold their ideas from leaders (Hamstra et al, 2021) and more likely to communicate them via voice behaviour (Gao et al, 2011;Ng & Feldman, 2013b, 2015.…”
Section: Predicting Voice Behaviour: the Mediating Role Of Affective Trust In The Leadermentioning
confidence: 99%
“…In our case, we included additional control variables (e.g. annual sales, service region and ownership) (Lu et al, 2018;Hamstra et al, 2021). The introduction of control variables in the existing model did not change the strength and significance of the relationships among variables.…”
Section: Structural Model Resultsmentioning
confidence: 99%
“…Recognizing the negative impact of narcissism on employees’ organizational behavior and emotions, Campbell et al (2010) suggested that organizational managers should improve their ability to identify narcissism in recruitment activities. However, although a large number of studies have confirmed the negative impact of narcissism on organizational development [e.g., Grijalva and Newman (2015) and Hamstra et al (2021) ], some scholars have pointed out that appropriate management practices for narcissists can enhance their initiative to a certain extent ( Falco et al, 2020 ; Mao et al, 2021 ). This study demonstrates the impact of supervisor support on the relationship between narcissism and organizational commitment, which also implies that resource support in the organization is an effective way to improve the emotion of narcissistic employees toward the organization ( Choi, 2019 ).…”
Section: Discussionmentioning
confidence: 99%